METODE PEMBELAJARAN AKTIF ALA RASULULLAH, PEMBELAJARAN YANG MEMBANGKITKAN MOTIVASI (Suatu Kajian Metode Pembelajaran dari Hadis) - . Salafudin (IAIN Pekalongan, 2011)
In the factual world of education, particularly the teachingmethods, it is said that the West is more advanced and moredeveloped than the Islamic world, undeniably, Islam contains a sourceof inspiration to develop science, especially the teaching methods.Departing from these concerns, this paper wants to give contributionto the world of Islamic education by trying to uncover the implicitlearning methods in the hadith, especially, active learning. Thousandsof prophetic hadith, contain a variety of rich values and act as asource of inspiration for developing this learning method. This paperaims to reveal the source in an attempt to formulate a more innovativeteaching methods by sticking to the teachings and values ofIslam. Main issue that is going to be studied in this paper is the activelearning methods as applied by the Prophet of Muhammad, SAWalong with the samples, and the implementation strategies of activelearning methods in education.